Training future clinicians in telehealth competencies: outcomes of a telehealth curriculum and teleOSCEs at an academic medical center - Bajra, Rika; Srinivasan, Malathi; Torres, Elise Cheng; Rydel, Tracy; Schillinger, Erika (Frontiers in Medicine, 2023)
Background This study describes the program and learning outcomes of a telehealth skills curriculum based on the Association of American Medical Colleges (AAMC) telehealth competencies for clerkship-level medical students. Methods A total of 133 third- and fourth-year medical students in a required family medicine clerkship at Stanford University School of Medicine participated in a telehealth curriculum, including a telehealth workshop, site-specific telehealth clinical encounters, and telemedicine objective structured clinical examinations (teleOSCEs) between July 2020 and August 2021. Their workshop communication and physical examination competencies were assessed in two teleOSCEs utilizing a novel telehealth assessment tool. Students' attitudes, skills, and self-efficacy were assessed through voluntary pre-clerkship, post-workshop, and post-OSCE surveys. Discussion Most learners reported low confidence in their telehealth physical examinations [n = 79, mean = 1.6 (scale 0–5, 5 = very confident, SD = 1.0)], which improved post-workshop [n = 69, 3.3 (0.9), p < 0.001]; almost all (97%, 70/72) felt the workshop prepared them to see patients in the clinic. In formative OSCEs, learners demonstrated appropriate “webside manner” (communication scores 94–99%, four items) but did not confirm confidentiality (21%) or review limitations of the visit (35%). In a low back pain OSCE, most learners assessed pain location (90%) and range of motion (87%); nearly half (48%) omitted strength testing. Conclusion Our telehealth curriculum demonstrated that telehealth competencies can be taught and assessed in medical student education. Improvement in self-efficacy scores suggests that an 80-min workshop can prepare students to see patients in the clinical setting. Assessment of OSCE data informs opportunities for growth for further development in the curriculum, including addressing visit limitations and confidentiality in telehealth visits.